Association of serum vitamin D concentration with the final course of hospitalization in patients with COVID-19 - Konikowska, Klaudia; Kiliś-Pstrusińska, Katarzyna; Matera-Witkiewicz, Agnieszka; Kujawa, Krzysztof; Adamik, Barbara; Doroszko, Adrian; Kaliszewski, Krzysztof; Pomorski, Michał; Protasiewicz, Marcin; Sokołowski, Janusz; Madziarska, Katarzyna; Jankowska, Ewa Anita (Frontiers in Immunology, 2023)
Background: Vitamin D deficiency is a substantial public health problem. The current study evaluated the association between vitamin D concentration and hospitalization and mortality risk in coronavirus disease 19 (COVID-19) patients. Methods: This study used the COronavirus in LOwer Silesia (COLOS) data set collected between February 2020 and June 2021. The medical records of 474 patients with confirmed severe acute respiratory syndrome 2 (SARS-CoV-2) infection, and whose vitamin D concentration was measured, were analyzed. Results: We determined a significant difference in vitamin D concentration between discharged patients and those who died during hospitalization (p = 0.0027). We also found an effect of vitamin D concentration on the risk of death in patients hospitalized due to COVID-19. As vitamin D concentration increased, the odds ratio (OR) for death slightly decreased (OR = 0.978; 95% confidence interval [CI] = 0.96-0.99). The vitamin D concentration cut-off point was 15.40 ng/ml. In addition, patients with COVID-19 and serum 25-hydroxyvitamin D (25(OH)D) concentrations < 30 ng/ml had a lower survival rate than those with serum 25(OH)D ≥ 30 ng/ml (log-rank test p = 0.0018). Moreover, a Cox regression model showed that patients with an estimated glomerular filtration rate (eGFR) ≥ 60 ml/min/1.73 m2 and higher vitamin D concentrations had a 2.8% reduced risk of mortality (hazard ratio [HR] = 0.97; CI = 0.95-0,99; p = 0.0097). Conclusions: The results indicate an association between 25(OH)D levels in COVID-19 patients and the final course of hospitalization and risk of death.